THE INTEGRATION OF CORPORATE SOCIAL - Ilett, Dominic Richard (My University, 2011)
While companies have been practising philanthropy for decades, the field of Corporate Social Responsibility (CSR) is a relatively new and fast evolving field in business. Companies invest ever increasing sums of money and resources in CSR; consequently, there is a need for companies to think strategically about their CSR approach to ensure its effective integration with overall business strategy. This research study documents how South African companies integrate CSR with their overall business strategy. By following a process of in-depth semi structured interviews, the views of senior executives and managers involved with CSR at companies listed on the Johannesburg Stock Exchange’s Social Responsible Investment Index were obtained. The main findings that emerged reveal that South African companies believe CSR should form part of company strategy. How companies set about making this a reality depends on their unique organisational structure. Importantly, it was found that an understanding of the external as well as internal forces impacting upon CSR, buy-in from leadership and all stakeholders and effective organisational processes and systems were critical for effective implementation. While some companies report having made progress, there is an acknowledgement that fully integrating CSR with company strategy has not yet been achieved
MBA - WBS
Keywords: Corporate social responsibility; Strategic planning